Analysis of Student Activity and Learning Outcomes in 21st-Century Innovative Learning with the PjBL Learning Model in 5th Grade of Elementary School - Istikomah Istikomah; Ana Andriani (UM Purwokerto Press, 2025)
This study began with observations at SDN Cinangsi 03, which revealed low student engagement in learning due to the limited application of 21st-century innovative approaches. The aim of this research, conducted in a 5th-grade elementary school, is to analyze the impact of project-based learning on student activity and learning outcomes on the topic